Carboxyl Methyltransferases: Natural Functions and Potential Applications in Industrial Biotechnology. Issue 1 (13th October 2020) - Ward, Lucy C.; McCue, Hannah V.; Carnell, Andrew J.
Abstract: The use of methyltransferases (MTs) in industrial biotechnology to replace toxic alkylating agents is of increasing interest. Carboxyl MTs (CMTs) are a subgroup of MTs that methylate the hydroxyl oxygen of carboxylic acids. Research initially focussed on their natural functions in protein regulation and production of volatile methyl esters in plants. In this review we highlight this potentially valuable group of enzymes that show promise for formation of a wide range of structurally diverse methyl esters from the parent acids under aqueous conditions. CMTs have been used to generate intermediates for biofuels, bioplastics and pharmaceuticals. These biocatalysts could also be integrated into cascades with other enzymes such as acyltransferases that function under aqueous conditions. Recent approaches for regenerating the required cofactor S ‐adenosylmethionine (SAM) are discussed including in vitro recycling, improvement in in vivo production and the use of more stable analogues. Advances in these areas will further improve the potential to use carboxyl MTs in industrial biotechnology. Abstract : Carboxyl methyltransferases (CMTs) methylate the hydroxyl oxygen of carboxylic acids. They are potentially useful biocatalysts in industrial biotechnology, facilitating the formation of methyl esters under aqueous conditions and could be integrated into multistep enzyme cascades, such as coupling with acyltransferases. CMTs have shown potential for the production of bioplastics, biodiesel and pharmaceuticals.